2020
DOI: 10.3390/ijerph17165942
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality among Women with Previous Gestational Diabetes Mellitus in Rural Areas of Hunan Province

Abstract: Diet quality is critical for postpartum type 2 diabetes mellitus (T2DM) progression among women with a history of gestational diabetes mellitus (GDM). The Chinese Healthy Eating Index (CHEI) is a dietary index developed according to the latest Chinese Dietary Guidelines (CDG-2016). Our study aimed to assess the diet quality of women with previous GDM in rural areas of Hunan Province by applying the CHEI. Women with previous GDM in two counties of Hunan were enrolled. Their food intake data, which were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…One study was reported over three separate articles which were identified by the search. Whilst each article was not individually eligible for inclusion, they were all included as the collated information provided in all of the articles facilitated eligibility [ 55 , 56 , 57 ]. One article was found to be a secondary analysis of a randomised controlled trial (RCT).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study was reported over three separate articles which were identified by the search. Whilst each article was not individually eligible for inclusion, they were all included as the collated information provided in all of the articles facilitated eligibility [ 55 , 56 , 57 ]. One article was found to be a secondary analysis of a randomised controlled trial (RCT).…”
Section: Resultsmentioning
confidence: 99%
“…One study was found which evaluated the role of the CHEI. The randomised controlled trial aimed to evaluate the effect of intensive lifestyle modifications in two centres within rural areas of Hunan Province, China, on physiological health outcomes including the development of T2DM and weight-related variables, and was reported over several articles by the group [ 56 ]. After the 6-month intervention, there were significant reductions in fasting blood glucose, 2-h glucose at OGTT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, although the government has established gender equality in legislation and granted women land rights; still women's rights concerns regarding their health, the voice for their rights are not supported and even taken for granted. Additionally, women in China residing in deprived rural areas have low health risk perceptions, putting their health conditions incredibly at worst for a long time ( Li et al, 2020). Although some scholars have discussed rural women's cognitive health (Ginja et al, 2020), nutritional status (Perkins et al, 2019), pregnant women's health rights (Bussink-Voorend et al, 2020), and food insecurity issues (Sinclair et al, 2019), as well as cooking fuels impacting women's health (Imran & Ozcatalbas, 2020) in the existing studies.…”
Section: Theoretical Analysis Of Risk Preference Health Risk Perceptions and Womenmentioning
confidence: 99%
“…Meanwhile, inequal health resources and a low level of health literacy are significant barriers to a healthy lifestyle in rural areas [ 22 , 23 ]. Our previous study has demonstrated unsatisfactory diet quality among women with previous GDM in rural regions [ 24 ]. Currently, there is no report relevant to lifestyle intervention for this special population in China.…”
Section: Introductionmentioning
confidence: 99%